Android Patient Manager Appplication Universitas Muhammadiyah Surakarta - Aridin, Sufian Salahuddin, Umi Fadlilah, S.T M.Eng (2016)
AndroidOperatingSystem is one of the biggest smartphones operating system in the mobile technology that penetrated into our societyfields. One of those fields is Medical/Healthcare technology that taking that penetrated system into it.Patient Manager is an application based on Android Operating System prepared with JAVA programing language and there will be JDK and JRE for java development environment side by side with Android Studio as IDE for developing android platform and an offline Database sqlite.Running the application with emulator or an android device for testing.The test result can be concluded that Android Patient Manager Application would save doctors time and reduces human interventions in collecting their patients data and it has been tested for the users and gave 60% satisfied result agreement.